Understanding the Resilience of Female Students Working in Occupational Health and Safety: A Qualitative Study - Grhasta Dian Perestroika; Niken Bayu Argaheni (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2025)
Background: Balancing dual roles as a professional and a student is a significant challenge, especially for women in the Occupational Health and Safety (OHS) field. Resilience is crucial for managing these responsibilities while ensuring workplace safety.Objective: This study examines the lived experiences of women pursuing postgraduate education while working full-time in OHS, focusing on factors contributing to resilience.Method: A qualitative phenomenological approach was used to explore participants' experiences. Two postgraduate students from Universitas Gadjah Mada, aged 18–45 years and actively employed in OHS, were recruited through purposive sampling. Semi-structured interviews were conducted via Zoom, addressing challenges, coping strategies, and institutional support. Data were analyzed using Braun and Clarke’s thematic analysis, with validation techniques including member checking and triangulation.Results: Four themes emerged: social support, adaptive coping strategies, self-efficacy, and institutional flexibility. Emotional support from family, practical assistance from colleagues, effective time management, self-reflection, and accommodating workplace policies were key enablers of resilience. These factors collectively supported participants in balancing dual roles while maintaining workplace safety.Conclusion: This study highlights the importance of targeted support systems to enhance resilience among working students in demanding fields like OHS. Insights from this research provide a framework for institutions and policymakers to address challenges and promote safer, healthier workplaces.